(untitled) (Annals of Medical Research, 2021)
Aim: Stroke ranks second among the causes of death world wideand related disability and death rates are high. Recent studies have shown that vitamin D deficiency is higher in patients with ischemic stroke compared to other patients and vitamin D deficiency has emerged as a new risk factor. The aims of the study are to investigate the relation between levels of vitamin D in patients diagnosed with acute ischemic stroke with levels of vitamin B12, glucose, HbA1c, blood urea nitrogen (BUN), creatinine, C-reactive protein (CRP) and lipids, and to determine the effect of vitamin D deficiency on other factors that increase the risk of acute ischemic stroke.Materials and Methods: Two thousand seven hundred thirty-four patients diagnosed with acute ischemic stroke were included in the study. Results of laboratory tests for levels of vitamin D, vitamin B12, HDL cholesterol, LDL cholesterol, VLDL cholesterol, triglycerides, glucose, HbA1c, BUN, creatinine and CRP were recorded.Results: As for correlation between vitamin D and other parameters, positive correlations between vitamin D and age, vitamin B12, BUN and creatinine, and negative correlations between vitamin D and triglycerides, LDL cholesterol, VLDL cholesterol, glucose, HbA1c and CRP were identified. Vitamin D and HDL cholesterol showed no correlation in normal HDL values, but there was positive correlation in patients with HDL cholesterol levels 40 mg/dL.Conclusion: Vitamin D levels in patients that suffered ischemic stroke were significantly correlated with lipid metabolism, glucose metabolism, inflammation, kidney function and vitamin B12 levels.